HUBUNGAN PERILAKU CARING PERAWAT DENGAN TINGKAT KEPUASAN PASIEN TRIAGE MERAH DI RUANG IGD RSUD RA. BASOENI KABUPATEN MOJOKERTO - Windartik, Emyk; Juwartiningsih, (JURNAL KEPERAWATAN SEHAT, 2016)
The behavior of caring is the nurses attention with a vengeance against the patient.Caring, empathy, communication is a gentle and compassion of nurses towards patients will form relationships of nurses – clients ar e therapeutic. but the reality in practice many still found less beperilaku nurse caring towards the patient. The purpose of the study to find out the relationship behavior caring nurse triage patient satisfaction with the level of red triage in the emergeny room at RA. Basoeni Hospitals Mojokerto. The design of the study was analytic korelasional with cross sectional approach . The population of this research the entire patient red triage in emergeny room at RA. Basoeni Hospitals Mojokerto as much as 125 patients in March 2016. Samples taken with the technique of concecutive sampling as much as 42 respondents. Study of variable behavior of caring nurse as the independent variable and the level of patient satisfaction as the dependent variable. The data collected with a questionnaire to conduct instrument caring and patient satisfaction. Then the results are tested with the coefficient contingenc test. Contingensy test results retrieved data ρ = 0.000 and α = 0.05 then ρ < α so that H0 is rejected ties mean there ¬ behavior caring nurse triage patient satisfaction with the level of red triage in the emergency room at RA. Basoeni Hospitals Mojokerto. Nurses who behave caring towards the nurses means patients are able to provide good service. By demonstrating caring behavior, then the nurse can provide a good experience for the patient. The more caring behaviors demonstrated by nurses in providing services it will provide satisfaction in patients so expect the hospital need to provide additional training and coaching to the nurses to be able to improve and maintain a good caring behavior through cooperation with relevant parties as well as independently.Key Words : Behaviours, Caring, Satisfaction, Red Triage